2007
DOI: 10.1152/ajpregu.00409.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased fatigue resistance of respiratory muscles during exercise after respiratory muscle endurance training

Abstract: Respiratory muscle fatigue develops during exhaustive exercise and can limit exercise performance. Respiratory muscle training, in turn, can increase exercise performance. We investigated whether respiratory muscle endurance training (RMT) reduces exercise-induced inspiratory and expiratory muscle fatigue. Twenty-one healthy, male volunteers performed twenty 30-min sessions of either normocapnic hyperpnoea (n = 13) or sham training (CON, n = 8) over 4-5 wk. Before and after training, subjects performed a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 50 publications
9
83
1
1
Order By: Relevance
“…cycle endurance at the anaerobic threshold (77% VO 2 max) was improved from 22.8 min to 31.5 min, while VO 2 max and the anaerobic threshold remained essentially the same [7]. The effects of IMT with flow resistance devices in cycle endurance athletes were connected with improving the time of sustained exercise intensity at the anaerobic threshold, while VO 2 max and the anaerobic threshold (VO 2 in % VO 2 max) remained basically unchanged [7,8,31]. Some studies show that IMT leads to an increase of aerobic power in hypoxic situations only [3].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…cycle endurance at the anaerobic threshold (77% VO 2 max) was improved from 22.8 min to 31.5 min, while VO 2 max and the anaerobic threshold remained essentially the same [7]. The effects of IMT with flow resistance devices in cycle endurance athletes were connected with improving the time of sustained exercise intensity at the anaerobic threshold, while VO 2 max and the anaerobic threshold (VO 2 in % VO 2 max) remained basically unchanged [7,8,31]. Some studies show that IMT leads to an increase of aerobic power in hypoxic situations only [3].…”
Section: Discussionmentioning
confidence: 94%
“…In healthy people and in athletes, the inability to sustain high levels of ventilation can restrict maximal aerobic capacity [7,12,31]. It has been shown that IMT without the addition of systemic exercise may result in quantitative outcomes [9,10,17,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have specifically trained the respiratory muscles have reported either an improvement (16,17,28,33,78,84,119,124,131) or no change (25,29,38,57,92,117,140) in whole body exercise tolerance. A concern with all of these studies, however, is that endurance performance was evaluated using fixed work-rate tasks sustained to the limit of tolerance.…”
Section: Overcoming the Respiratory Limitations To Exercisementioning
confidence: 99%
“…The ergogenic effect could be due to relief of respiratory muscle fatigue (105,131) or limb muscle fatigue (81), perhaps by attenuation of the respiratory muscle metaboreflex (142). However, the perceptual benefit obtained through relieving the discomfort associated with high levels of respiratory muscle work may also be responsible for at least some of the improvement in exercise performance (82).…”
Section: Overcoming the Respiratory Limitations To Exercisementioning
confidence: 99%
“…Respiratory muscle training can reduce or delay the development of respiratory muscle fatigue Verges et al, 2007;Verges et al, 2009). This in turn may prevent the development of rapid and shallow breathing as shown in some (Spengler et al, 1999;Volianitis et al, 2001;Amonette and Dupler 2002;Wylegala et al, 2007;Esposito et al, 2010) but not in other (Kohl et al, 1997;Stuessi et al, 2001;Volianitis et al, 2001;McMahon et al, 2002;Holm et al, 2004;Griffiths and McConnell 2007;Verges et al, 2007;Brown et al, 2010;Ray et al, 2010) studies.…”
Section: Introductionmentioning
confidence: 99%